2011
DOI: 10.1536/ihj.52.382
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Lymphocytes Attenuate Myocardial Infarction-Induced Ventricular Remodeling in Mice

Abstract: SummaryDownregulation of CD4+CD25+ regulatory T lymphocytes (Treg) has been found in local atherosclerotic lesions and in patients with myocardial infarction (MI). However, the roles of Treg in MI and the following inflammatory response have not yet been well elucidated. Therefore, we hypothesized that adoptive transfer of Treg could attenuate the postinfarction inflammatory response protecting from adverse remodeling, and we attempted to elucidate the mechanism of delayed heart failure after MI. To clarify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 24 publications
0
74
0
4
Order By: Relevance
“…13) Matsumoto, et al also reported that transfer of Tregs attenuated myocardial infarction-induced ventricular remodelling in mice. 14) These fi ndings suggest that peripheral circulating Tregs might be involved in the pathogenesis of left ventricular dysfunction during development of heart failure.…”
Section: Cd4mentioning
confidence: 95%
“…13) Matsumoto, et al also reported that transfer of Tregs attenuated myocardial infarction-induced ventricular remodelling in mice. 14) These fi ndings suggest that peripheral circulating Tregs might be involved in the pathogenesis of left ventricular dysfunction during development of heart failure.…”
Section: Cd4mentioning
confidence: 95%
“…Accordingly, a single adoptive Treg transfer in a permanent MI mouse model attenuates both the postinfarction inflammatory response and adverse remodeling. 53 However, none of these results define how Tregs exert their beneficial effects. Unanswered questions of particular importance include how therapeutically activated/transferred Tregs interfere with the protective activation of adaptive T-cell immunity as demonstrated in response to MI 20 and how Tregs interact with innate leukocytes.…”
Section: Cd4mentioning
confidence: 99%
“…53 The mechanism behind these results is not clear, especially because the number of transferred cells only modestly adds to the endogenous Treg pool. Furthermore, most clinical trials of adoptive Treg therapy fail to achieve long-term cell engraftment or substantial clinical benefit, particularly for treating graft versus host disease and type I diabetes mellitus.…”
Section: T-cells As Therapeutic Targetsmentioning
confidence: 99%
“…2,3 However, a role for adaptive immunity responding to damage has also been suspected with protection from MI in animals treated with adoptive transfer of regulatory T cells. 4 Two recent studies show that both dendritic cells (DCs) 5 and T cells 6 are required for proper cardiac remodeling after MI and can play a beneficial role. These 2 studies have remarkably similar phenotypes.…”
Section: Article See P 1652mentioning
confidence: 99%